Cell wall O-glycoproteins and N-glycoproteins: aspects of biosynthesis and function - Nguema-Ona, Eric; Vicré-Gibouin, Maïté; Gotté, Maxime; Plancot, Barbara; Lerouge, Patrice; Bardor, Muriel; Driouich, Azeddine (Frontiers in Plant Science, 2014)
Cell wall O-glycoproteins and N-glycoproteins are two types of glycomolecules whose glycans are structurally complex. They are both assembled and modified within the endomembrane system, i.e., the endoplasmic reticulum (ER) and the Golgi apparatus, before their transport to their final locations within or outside the cell. In contrast to extensin, the O-glycan chains of arabinogalactan proteins are highly heterogeneous consisting mostly of (i) a short oligo-arabinoside chain of three to four residues, and (ii) a larger -1,3-linked galactan backbone with -1,6-linked side chains containing galactose, arabinose and, often, fucose, rhamnose or glucuronic acid. The fine structure of arabinogalactan chains varies between, and within plant species, and is important for the functional activities of the glycoproteins. With regards to N-glycans, ER-synthesizing events are highly conserved in all eukaryotes studied so far since they are essential for efficient protein folding. In contrast, evolutionary adaptation of N-glycan processing in the Golgi apparatus has given rise to a variety of organism-specific complex structures. Therefore, plant complex-type N-glycans contain specific glyco-epitopes such as core 1,2-xylose, core 1,3-fucose residues and Lewisa substitutions on the terminal position of the antenna. Like O-glycans, N-glycans of proteins are essential for their stability and function. Mutants affected in the glycan metabolic pathways have provided valuable information on the role of N-/O-glycoproteins in the control of growth, morphogenesis and adaptation to biotic and abiotic stresses. With regards to O-glycoproteins only extensin and arabinogalactan proteins are considered herein. The biosynthesis of these glycoproteins and functional aspects are presented and discussed in this review.